Using student perceptions of the learning environment to evaluate the effectiveness of a teacher professional development programme - Soebari, T.; Aldridge, Jill (Kluwer Academic Publishers, 2015)
The focus of this article is two-fold. First, it describes a model that can be used to guide the evaluation of teacher professional development. The model combines important components of existing models and incorporates the use of students’ perceptions for examining teacher change. Second, the article reports the evaluation of a teacher development programme that incorporated this model. In particular, this article focuses on the phases of the model that involved student perceptual measures. Using a pre-post design, the evaluation involved quantitative (students’ perceptions of the learning environment) and qualitative (observation and interview) data in investigating whether teaching practices changed over the course of a 1-year professional development programme. Data were collected before the commencement of the professional development programme and at the end of the programme from students in two classes of each of 33 teachers who attended the professional development programme (N = 2,417). These data were analysed using one-way MANOVA to provide a large-scale overview of the pre-post differences in students’ perceptions of their learning experience. Although there were statistically significant changes for six of the seven WIHIC scales (with all statistically significant differences showing an improvement), the effect sizes for all scales were too small (according to Cohen’s criteria) to be considered educationally important. These findings, that the success of the teacher professional development programme could have been limited, were corroborated by observations. Further, interviews with teachers provided information about contextual factors that influenced the translation of the professional development ideas into practice.